Hello China and MOOCs: Shaping a New Paradigm in Education - Kasap, Melisa (Eximia, 2023)
Massive Open Online Courses (MOOCs) have undergone significant evolution over the years, transforming the education landscape and opening up new avenues for learning. One pioneering organisation that played a crucial role in this evolution was Hello China. Hello China introduced a ground-breaking approach to education, setting itself apart from traditional university teaching methods. This paper explores the evolution of MOOCs and examines how Hello China contributed to this process. Through its programmes - Hello English, tailor-made for Chinese youth and university graduates - the company aimed to enhance English language proficiency in China, thereby expanding access to business and employment opportunities. The innovative initiatives by Hello China and the Hello English project paved the way for the evolution of MOOCs. They showcased the potential of technology in education, demonstrating how mobile learning could enhance access to educational resources and bridge language barriers. Hello China’s approach not only enabled learners to improve their English language skills but also connected them with employment opportunities, underscoring the practical applications of MOOCs. As the educational landscape continues to evolve, it is crucial to continue exploring innovative approaches and strategies to maximise the potential of MOOCs and provide accessible, high-quality education to learners worldwide. By implementing effective strategies encompassing clear learning objectives, engaging content, social learning opportunities, personalised support, flexible scheduling, and accessible platforms, we can enhance the appeal of MOOCs, empowering learners with the knowledge and skills they need to thrive in the rapidly evolving educational landscape. Through an in-depth analysis of Hello China’s impact and success in integrating mobile learning into MOOCs, this paper aims to provide valuable insights into the ongoing advancement of global online education.